Perancangan Profil Target Audience Pada Facebook Ads untuk Toko Online XYZ - Sari, Hasrini; Salim, Airin Levina; Setiaboedi, Aditya Parama (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2021)
XYZ online shop is one of SMEs that sell women's shoes online. Since the first product was released in May 2018, XYZ online shop sales have increased. This encourages XYZ online shop’s owner dare to target high sales this year at 50,000 pairs. The main challenge that faced by XYZ online shop in achieving these targets is in conducting marketing activities. Marketing activities carried out by XYZ online shop is using social media marketing such as Facebook Ads. XYZ online shop’s owner still feels confused to formulate the target audience in making the ad, especially in determining the profile of target audience. First, cluster analysis is performed using fashion lifestyle variables as the basis for segmentation. Psychographic, demographic and purchasing behavior variables used to describe the cluster. Clusters that formed are indifferent with fashion, fashion oriented with regular purchase, dan fashion oriented with high purchase power. Fashion oriented with regular purchase cluster was chosen to become owner’s focus. Then, detailed targeting on Facebook Ads was designed based on the characteristics of the cluster. At last, ad test is carried out and the result is ad with detailed targeting profile audience has the lowest cost per result.